(untitled) (Journal of Health Sciences, 2020)
Introduction: Normative data on handgrip strength (HGS) and body mass index (BMI) are scarce among adolescents in the Nigerian context. The aims of this study were to evaluate patterns of HGS in relation to gender and age in Nigerian adolescents and its correlation with BMI.Methods: This cross-sectional study involved 1966 participants (1275 males) and (691 females) aged 12–20 years in Northern Nigeria. Body mass and height were measured. HGS was assessed using a dynamometer.Results: The right HGS (RHGS) was significantly higher than the left HGS (LHGS) (t = 21.337, p < 0.05). There were significant age differences in the RHGS and the LHGS (p < 0.05); however, no significant difference occurs at 12–14 years. Males participants aged 16–20 years had significantly higher RHGS values than females of the same age (p < 0.0038). Conversely, males aged 15–20 years had significantly higher LHGS values than females of the same age (p < 0.0038). There was a significant interaction between gender and age for the RHGS (F = 72.2, p < 0.05) and the LHGS (F = 92.1, p < 0.05). There was a significant correlation between the BMI and RHGS (r = 0.480, p < 0.01) and the LHGS (r = 0.465, p < 0.01).Conclusion: There are gender and age difference in the HGS of Nigerian adolescents, with the dominance of the RHGS in both genders. HGS correlated with BMI. This normative data on HGS may serve as baseline data for future comparative studies assessing HGS among the adolescent population in Nigeria.